2015
DOI: 10.1515/pjph-2015-0046
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and stress in miscarriage

Abstract: Miscarriage is defined as an adverse and unexpected termination of pregnancy before the completion of 22 nd week of gestation. Currently, abortion is the most common early reproductive failure. In Poland, more than 40 000 pregnant women a year lose pregnancy due to various reasons. There are many reports in literature on the risk of somatic consequences of miscarriage, while extra-somatic complications resulting from exposure to the strong influence of anxiety and stress, such as, for example: depression and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
1
14
1
Order By: Relevance
“…Our finding that unmarried women are less likely to experience stillbirths compared to married women contradict the findings of previous studies that identified higher risk of stillbirths among unmarried women compared to married women [37,38]. We argue that just like miscarriages, stillbirths are also natural events and women who experience stillbirth may have been exposed to risk factors such as stress from their partners, families or struggling to meet routine deadlines at work as established in the literature [33][34][35] and these stressful events are more likely to occur in marriages. In relation to our finding that the odds of stillbirth is lower among women with higher parity, it contradicts the findings of studies that have identified that high chances of stillbirth characterise women with multiple pregnancies [39][40][41] and those that have found a u-shaped relationship between parity and stillbirths [42,43].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Our finding that unmarried women are less likely to experience stillbirths compared to married women contradict the findings of previous studies that identified higher risk of stillbirths among unmarried women compared to married women [37,38]. We argue that just like miscarriages, stillbirths are also natural events and women who experience stillbirth may have been exposed to risk factors such as stress from their partners, families or struggling to meet routine deadlines at work as established in the literature [33][34][35] and these stressful events are more likely to occur in marriages. In relation to our finding that the odds of stillbirth is lower among women with higher parity, it contradicts the findings of studies that have identified that high chances of stillbirth characterise women with multiple pregnancies [39][40][41] and those that have found a u-shaped relationship between parity and stillbirths [42,43].…”
Section: Discussioncontrasting
confidence: 92%
“…In terms of age, marital status and miscarriage, miscarriage has been considered as a natural event and women who experience miscarriage might have been exposed to risk factors that they may even not be aware of. Such risk factors often include stress from their partners, families or struggling to meet routine deadlines at work as established in the literature [33][34][35] and these occur among older women who are also more likely to be married. The association between high parity and reduced likelihood of miscarriage has been reported by Shaimaa and Shukriya [36].…”
Section: Discussionmentioning
confidence: 99%
“… OR No 6 Boyles SH 8 USA 1995–1997 Nested case-control 970 970 Life events Women maintained their pregnancy A modified life event inventory (the participants were questioned about different categories of major life events, including death,debt burden, legal problems, and personal relationships). OR Tobacco use, cocaine use, alcohol use, prenatal care, living with the father 9 Brandt L, 1992 12 Denmark 1983–1985 Cohort 6945 4500 Work stress ND A questionnaire about stress-related job characteristics (a questionnaire about the information on occupational status, job title, stress-related job characteristics, ergonomic work load, exposure to organic solvents, exposure to video display terminals, lifestyle factors, and health factors during pregnancy). OR Previous pregnancies 6 Fenster L, 1995 22 USA 1990–1991 Cohort 3953 3953 Work stress Women maintained their pregnancy An abbreviated version of instrument (the instrument is based on the concepts that job stress results from high psychological demands in combination with low control over those demands and that social support at work can ameliorate the effects of stressful work).…”
Section: Resultsmentioning
confidence: 99%
“…Stress (e.g. financial or marital problems, death, divorce, physical and nonphysical abuse inflicted on a woman by her partner and loss of social support) was also associated with the likelihood of miscarriage among women reporting to an emergency department or admission to hospital 10 , 11 .Psychological challenges can include the experience of emotional trauma, social problems, concerns about money, marital/partnership disharmony, work pressure, significant change in personal circumstances as well as prior pregnancy loss 12 . In addition, retrospective studies link increase in workplace demands with adverse pregnancy outcomes including miscarriage 7 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with normal pregnant women, women who have had a diagnosis of foetal abnormality are four times more likely to be diagnosed with postpartum depression and seven times more likely to be diagnosed with post-traumatic stress disorder (Gold, Leon, Boggs, & Sen, 2015). Importantly, the discovery of a foetal abnormality may elicit destructive psychological problems and negative emotions such as anxiety, depression and dissatisfaction for those women (Kicia, Skurzak, Wiktor, Iwanowicz-Palus, & Wiktor, 2015;Krosch & Shakespeare-Finch, 2017;Silva Lima et al, 2016;Sun et al, 2020;Yu & Hu, 2013). These symptoms might persist until the next pregnancy (Fernández Ordóñez, Rengel Díaz, Morales Gil, & Labajos Manzanares, 2018).…”
Section: Introductionmentioning
confidence: 99%